An Advanced Magnetoelastic (ME) Sensing of Salmonella by the Improvement of Pathogen Recovery Rate Using Tween20 Modified Swabs. (19th June 2018) - Liu, Yuzhe; Du, Songtao; Horikawa, Shin; Chen, I-Hsuan; Xi, Jianguo; Huang, Tung-Shi; Chin, Bryan A.
Abstract : Swabbing, as an inexpensive, easy-to-use, and widely accepted sampling method, has been used to help magnetoelastic (ME) biosensing system for the surface pathogen quick detection. This paper introduced a modification method using a surfactant, Tween20, to help to improve the recovery rate of different swabs. In our previous research, swabbing substituted the direct ME sensor detection on the sample surfaces, which improved the detection area of one sensor from 0.2X1 mm 2 into 30X30 mm 2 . This amendment altered the previous surface spot measurement into a large area measurement. To improve the accuracy of this swabbing technique to a better level, a higher recovery rate is needed. Tween20, a stable and relatively non-toxic surfactant, was employed to modify the fibers of swabs so that after the pathogens are picked up, they would be easier to be released into DI water and detected by ME sensors. In this research, traditional swabs, such as cotton-tipped, rayon-tipped, and novel flocked swabs are used for comparison.